A Study to Assess Prevalence of Tobacco Use Among Adolescents and Assess the Effectiveness of Structured Teaching Program Regarding Ill Effects of Tobacco Use and Its Prevention Among Adolescents in Selected Community of New Delhi - Anjali Samson; Sumity Arora; Thresiamma George (International Journal of Community Health Nursing And Practices, 2023)
Tobacco use among adolescents has become a global challenge and it is reaching pandemic levels. The objectives of the study were (a) to assess the prevalence of tobacco use among adolescents in a selected community of New Delhi, (b) To provide an organised education programme on the negative effects of tobacco smoking and how to prevent it for teenagers in a chosen New Delhi community, (c) to determine whether the organised education approach was successful in increasing adolescent knowledge of the negative effects of tobacco use and how to prevent it, (d) to determine whether the pre-test knowledge score correlates with the chosen demographic variables for teenagers. Materials And Methods: The research approach selected for this was quantitative research approach. The present study employs a two-phase research design. Phase I: A descriptive, non-experimental study, and Phase II: A preliminary, one-group, pre-test, post-test study. The sample was adolescents between 13 to 19 years of age. In Phase I, 200 adolescents were selected by purposive sampling technique and 118 adolescents were identified cases selected by total enumeration sampling technique in phase II. The instruments utilized in the study included a structured prevalence questionnaire, a structured knowledge questionnaire, and a structured teaching program. The pilot study was conducted to ascertain feasibility of the study Result and Conclusion: The results of Phase I revealed that majority of adolescent are at risk of prevalence regarding tobacco use among adolescents. An organised teaching strategy was shown to be beneficial in terms of knowledge gain as the mean. Pre-test knowledge score significantly correlated with a chosen demographic factor.
Keywords: Adolescents; Delhi; Structured teaching programme; tobacco